Contribution to the taxonomy of Oxytrigona Cockerell, 1917 (Apidae, Meliponini) - Lepeco, Anderson (Zootaxa, 2024)
The stingless bees of the genus Oxytrigona Cockerell are popularly known as “fire bees”, due to their unique habit of spitting a caustic secretion when disturbed. Currently, this neotropical genus includes 11 valid species distributed from southern Brazil, throughout most of South and Central America, reaching southern Mexico. They are especially diverse in the Amazon, where five species are recorded. Although Oxytrigona exhibits a very distinctive morphology in relation to other stingless bees, species are often difficult to identify, having blurred limits due to intraspecific variation. In the present contribution the taxonomy of Oxytrigona is revisited, based on novel findings since the last taxonomic accounts were made. Oxytrigona tataira (Smith, 1863) is reinterpreted on the basis of new evidence regarding the provenance of its type material. The whereabouts of the type material of Oxytrigona cagafogo (Müller, 1874) sp. ressur. are discussed, and the species is resurrected from synonymy, representing a common bee occurring in the Atlantic rainforest of Brazil. Oxytrigona huaoranii Gonzalez & Roubik, 2008 is considered a junior synonym of Oxytrigona mellicolor (Packard, 1869) syn. nov., and the identity of the species is clarified. The whereabouts of the type material of Oxytrigona flaveola (Friese, 1900) are discussed. Three new species are described: Oxytrigona banana sp. nov. from Brazil and Paraguay; Oxytrigona pallida sp. nov. from northern South America and Central America; and Oxytrigona sauronica sp. nov. from Colombia. Distribution maps and a revised key are provided. Although the taxonomy of Oxytrigona species has been improved, questions remain about some species complexes. Implementation of tools from phylogeography is encouraged in order to improve our understanding of the species boundaries.